Anaesthetic management of emergency exploratory laparotomy for ruptured ectopic pregnancy in a patient with Ebstein’s anomaly and Wolff-Parkinson-White syndrome: a challenge for the anaesthesiologists - Singh, Pooja; Dwivedi, Sudhakar; Dwivedi, Rajeev; Yadav, Avtar (International Journal of Research in Medical Sciences, 2017)
Ebstein's anomaly (incidence 1:110,000) is characterized by the downward displacement and elongation of the tricuspid valve with poorly contractile right ventricle, an enlarged right atrium along with tricuspid regurgitation. It has shown particular association with Wolf-Parkinson-White syndrome (up to 20 % of patients). Wolff-Parkinson-White syndrome (WPW syndrome) is a rare cardiac anomaly characterised by aberrant conduction pathway between atria and ventricles. Here we describe the successful management of a patient with Ebstein’s anomaly and co-existing WPW syndrome, who presented in our institute with ruptured ectopic pregnancy and was posted for emergency exploratory laparotomy. The anaesthetic management of these patients is very challenging as they can develop life threatening tachyarrthmias like atrial fibrillation (AF) and paraoxysmal supraventricular tachycardia (PSVT).